Talent Management Practices and Employee Engagement-A Study in Malaysian GLCs - Voon Li Qi; Cheong Jia Qi (Universiti Malaysia Sabah, Kota Kinabalu, Sabah, 2021)
Talent management and employee engagement have been widely studied in academic literature. Talent management issues and employee engagement are becoming critical workforce management challenges at workplace. This is because when engagement of employee affected caused by talent management issues such as bureaucratic meddling, unfairness distribution of compensation and evaluation of employee performance as result disrupt working routines of other workforce, increase attrition of talented workforce and affected organization growth and performance. There are many organizations from other country also occurred issues of talent management included GLCs Malaysia. This study aims to understand the influence of talent management and investigate how talent management affects employee engagement in GLCs Malaysia. It is also to determine the relationship between talent management and employee engagement as well as to analyze strategies used to increase employee engagement in GLCs Malaysia. In order to achieve the objectives of case study, a literature review was conducted to provide a better understanding of talent management and employee engagement and identify the issues of talent management that affect employee engagement. Moreover, the findings indicate that the talent management issues such as bureaucratic meddling, ineffective performance management system (PMS), talent retention and talent shortage have positive relationship with employee engagement. Hence, this study recommends that GLCs Malaysia to increase levels of employee engagement need to establish a clear line of authority with well-defined hierarchical management system to avoid bureaucratic among employees with using Max Weber Theory, have fairness of performance management system (PMS) to overcome ineffective PMS, to identify and understand the workforce needs and wants to increase employee job satisfaction in retaining qualified talents by using Maslow Hierarchy of Needs and acquire the right talent and remain on the jobs to minimize the issue of talent shortage by using 4Bs Model. Finally, the research provide some suggestions for future researchers to improve the understanding of talent management practices which impacts on employee engagement.